Acute Hemorrhage into Adrenal Pseudocyst Presenting with Shock: Diagnostic Dilemmas Report of Three Cases and Review of Literature - Amarapathy Sivasankar; Sathyanesan Jeswanth; Maria Antony Johnson; Palaniappan Ravichandran; Shanmugasundaram Rajendran; Devy Gounder Kannan; Rajagopal Surendran (The Scientific World Journal)
We report three cases of acutely bleeding adrenal pseudocysts presenting as hemorrhagic shock. Pregnancy was associated in two cases. The diagnostic dilemmas are discussed with special reference to their unusual presentations, diagnosis, and treatment. We believe that our cases, complicated by intracystic hemorrhage, may be related to pregnancy.